Smashy town - Zimmerman, Andrea Griffing; Clemesha, David (Harper, an imprint of HarperCollinsPublishers, 2020)
"With a turn of his crane and a swing of his wrecking ball, Mr. Gilly knocks down the old buildings. He smashes through brick and wood. He crashes through stone and glass. Then, with a push from his bulldozer, Mr. Gilly cleans it all up to make room for something brand-new!" -- Amazon.